Protegrin-1 Regulates Porcine Granulosa Cell Proliferation via the EGFR-ERK1/2/p38 Signaling Pathway in vitro - Pan, Bo; Liu, Canying; Zhan, Xiaoshu; Li, Julang (Frontiers in Physiology, 2021)
Antimicrobial peptides (AMPs) are traditionally known to be essential components in host defense via their broad activities against bacteria, fungi, viruses, and protozoa. Their immunomodulatory properties have also recently received considerable attention in mammalian somatic tissues of various species. However, little is known regarding the role of AMPs in the development and maturation of ovarian follicles. Protegrin-1 (PG-1) is an antimicrobial peptide which is known to have potent antimicrobial activity against both gram positive and negative bacteria. Here we report that the PG-1 is present in the porcine ovarian follicular fluid. Treatment of granulosa cell with PG-1 enhanced granulosa cell proliferation in a dose-dependent manner. This is accompanied by increased expression of cell-cycle progression-related genes such as cyclin D1(CCND1), cyclin D2 (CCND2), and cyclin B1(CCNB1). Additionally, Western blot analysis showed that PG-1 increased phosphorylated epidermal growth factor receptor (EGFR), and the phosphorylated-/total extracellular signal-regulated kinase (ERK)1/2 ratio. Pretreatment with either U0126, a specific ERK1/2 phosphorylation inhibitor, or EGFR kinase inhibitor, AG1478, blocked the PG-1 induced proliferation. Moreover, luciferase reporter assay revealed that ETS domain-containing protein-1 (Elk1), C/EBP homologous protein (CHOP), and the transcription activators downstream of the Mitogen-activated protein kinase (MAPK) pathway, were activated by PG-1, These data collectively suggest that PG-1may regulate pig granulosa cell proliferation via EGFR-MAPK pathway. Hence, our finding offers insights into the role of antimicrobial peptides on follicular development regulation.